Nutritional Status Profile based on Anthropometry in Nutrition Study Program Students at State University of Malang - Ilmi Dewi Astuti (Universitas Negeri Medan, 2023)
Nutritional problems such as obesity, overnutrition and undernutrition are still found in developing countries today. The World Health Organization (WHO) predicts that by 2030, the prevalence of obesity in Indonesia will be 14% for women and 10% for men. In several countries the prevalence of overweight and obesity has increased in children and adolescents during the COVID-19 pandemic. The purpose of this study was to describe the nutritional status based on anthropometry in students of the Nutrition Study Program, State University of Malang. This research is a descriptive research with 30 students of nutrition study program as subjects selected with purposive sampling method. From the results of the study, it was found that as many as 80% of respondents had normal nutritional status, 10% of respondents had obese nutritional status, 7% of respondents had overweight nutritional status and 3% of respondents had thin nutritional status. The conclusion that can be drawn is that the majority of nutrition study program students at State University of Malang have normal nutritional status